2020
DOI: 10.3390/ijerph17051808
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact and Equity of an Integrated Rural Sanitation Approach: A Longitudinal Evaluation in 11 Sub-Saharan Africa and Asian Countries

Abstract: Few rural sanitation programs have documented large increases in sanitation coverage or have assessed if interventions equitably increase sanitation coverage for vulnerable groups. We characterize the impact of the Sustainable Sanitation and Hygiene for All (SSH4A) approach on key program WASH (water, sanitation, and hygiene) indicators, and also assess if these increases in WASH coverage are equitably reaching vulnerable groups. The SSH4A approach was administered in 12 program areas in 11 countries, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 23 publications
1
52
2
Order By: Relevance
“…Changes were much lower than with approaches found by Crocker et al elsewhere in Ethiopia [34,37]. Similarly, Apanga et al found that implementation of the Rural Sustainable Sanitation and Hygiene for All (SSH4A) approach that employs a multidimensional intervention led to a large increase of 77 percentage points in sanitation coverage in Ethiopia and also coverage gains in many other countries under study [60], although slippage did occur after conclusion of program activities, whereas many other countries sustained their previous sanitation coverage gains [61].…”
Section: Discussionmentioning
confidence: 98%
“…Changes were much lower than with approaches found by Crocker et al elsewhere in Ethiopia [34,37]. Similarly, Apanga et al found that implementation of the Rural Sustainable Sanitation and Hygiene for All (SSH4A) approach that employs a multidimensional intervention led to a large increase of 77 percentage points in sanitation coverage in Ethiopia and also coverage gains in many other countries under study [60], although slippage did occur after conclusion of program activities, whereas many other countries sustained their previous sanitation coverage gains [61].…”
Section: Discussionmentioning
confidence: 98%
“…Water, Sanitation and Hygiene, commonly known as WASH have been the focus of many researchers in Africa in recent times ( Sanou et al, 2015 ; Elisante and Muzuka, 2016 ; Metwally et al, 2007 ; Adams, 2018 ; Back et al, 2018 ; Nhamo et al, 2019 ; Sunkari and Abu, 2019 ; Zango et al, 2019 ; Abanyie et al, 2020 ; Apanga et al, 2020 ; Mutono et al, 2020 ; Sunkari et al, 2020 ). Globally, it is well established that poor sanitation, unhygienic conditions and lack of quality water supply have been the cause of many illnesses and deaths.…”
Section: Sustainable Remedial Measures Of Sars-cov-2 Transmission In mentioning
confidence: 99%
“…The available sanitation research overwhelmingly comprises of case studies that most commonly draw on household-level micro-data. A few studies have investigated international and sub-national geographical inequalities in sanitation conditions [50,51,52,53], while some have also analyzed the various sanitation determinants [54,20,49]. The research focusing on the meso-and macro-level patterns of OD practices is generally scanty and rather descriptive, being often limited to simply monitoring basic sanitation indicators [55].…”
Section: Notementioning
confidence: 99%